2015
DOI: 10.1007/s13277-015-3954-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic efficacy of γ-radiation together with gallium trichloride and/or doxorubicin against Ehrlich carcinoma in female mice

Abstract: Combining chemotherapy with radiotherapy represents a key oncology strategy for a more comprehensive attack toward cancers and improves treatment outcome for various solid tumor malignancies. The present study aims to evaluate the synergistic antitumor effect of γ-radiation together with gallium trichloride (GaCl3) and/or doxorubicin (DOX) against solid Ehrlich carcinoma (EC) in female mice. GaCl3 (300 mg/kg body weight (b.w.)) was administered by gavages daily on the seventh day after tumor inoculation, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Serum CPK, AST and LDH activities are used clinically to evaluate and diagnose cardiac dysfunction and disease. The present data showed that, serum AST, CPK and LDH activities were significantly elevated in EC and EC+ Dox groups compared to normal control group and these results correlate well with others [39,44] . The data presented here showed that, the administration of GaCl 3 alone or combined with Dox showed marked decrease in the activities of serum AST, CPK and LDH compared to both EC and EC+Dox groups.…”
Section: •-[39]supporting
confidence: 90%
“…Serum CPK, AST and LDH activities are used clinically to evaluate and diagnose cardiac dysfunction and disease. The present data showed that, serum AST, CPK and LDH activities were significantly elevated in EC and EC+ Dox groups compared to normal control group and these results correlate well with others [39,44] . The data presented here showed that, the administration of GaCl 3 alone or combined with Dox showed marked decrease in the activities of serum AST, CPK and LDH compared to both EC and EC+Dox groups.…”
Section: •-[39]supporting
confidence: 90%
“…Administration of GaNPs and/or R exposure to tumor-bearing mice significantly decreased calcium concentration in liver and tumor tissues in the treated groups (EC + R, EC + GaNPs, and EC + GaNPs + R) compared to EC group, and this result is consistent with others. 51,52 Gallium appears to be a uniquely acting agent for treatment of bone-resorptive conditions reducing accelerated bone loss in patients with cancer. In contrast to other calcium-saving drugs, gallium enhances calcium and phosphorus content of the bone and has direct, non-cytotoxic effects on osteoclasts at markedly low doses, and it is well established that the mechanism involves gallium insertion into the hydroxyapatite matrix protecting it from resorption and improving biomechanical properties of the skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other calcium-saving drugs, gallium enhances calcium and phosphorus content of the bone and has direct, non-cytotoxic effects on osteoclasts at markedly low doses, and it is well established that the mechanism involves gallium insertion into the hydroxyapatite matrix protecting it from resorption and improving biomechanical properties of the skeletal system. 52 Low-dose ionizing radiation suppressed intracellular Ca 2+ influx. It was found that vRBL-2H3 cell line exposed to ionizing radiation in the range of 0.01–0.5 Gy showed decrease in the levels of calcium influx in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…EAC cells are of mammary origin. 16 The viability of the cells was 99% as judged by trypan blue exclusion assay. The xenograft model of Ehrlich solid tumor (EST) was induced in female Swiss albino mice by viable EAC cells (about 2.5 × 106/mouse) in 0.2 mL isotonic saline implanted subcutaneously (sc) into the right thigh of the hind limb of each mouse.…”
Section: Solid Tumor Inductionmentioning
confidence: 99%